Actuation design and assistive control for a soft wearable exosuit - Dinh, Binh Khanh (2018)
The development of a portable assistive device to aid patients affected by neuromuscular disorders has been the ultimate goal of assistive robots since the late 1960s. Traditional robotic devices have been engineered to assist the users' limbs in both activities of daily living (ADLs) and physical therapy, mostly consisting of load-bearing exoskeletons made of rigid links that operate in parallel to the human skeleton. These devices can be extremely accurate and are able to deliver high forces/torques to their users, making them optimal solutions for improving physical therapy in clinical environments. However, their structural complexity cause them to be poor candidates for daily at-home use, where portability, lightweight, compliance, and low profile are preferable.